Лінгвостилістика в контексті загального мовознавства - Єрмоленко, С.Я. (Мовознавство, 2017)
У статті йдеться про статус лінгвостилістики як окремої галузі мовознавства; про категорії лінгвостилістики, визначення стилю, стилістичних функцій мовних одиниць і системи функціональних стилів літературної мови. Обґрунтовано зміну наукової парадигми лінгвостилістичних досліджень, пов’язану з інтегруванням стилістики й текстології, стилістики і гуманітарних наук — філософії, психології, культурології. The article deals with the status of linguistic stylistics as a separate branch of linguistics; the categories of linguistic style, the definition of style, the stylistic functions of the lingual units and the system of functional styles of the literary language. The scientific paradigm change of linguistic-stylistic researches related to the integration of stylistics and textology, stylistics and the humanities - philosophy, psychology, and culture studies is substantiated. The arguments concerning the incorrect use of die word «speech» in the Ukrainian scientific terminology, as well as the practice of artificial contrasting stylistics of language and stylistics of speech are presented. The categorical content of such concepts of linguistic stylistics is revealed: level stylistics or structural stylistics, functional stylistics, style of text (artistic text), communicative stylistics, cognitive stylistics, stylistics of decoding and stylistics of coding (creation) of text, comparative stylistics, historical stylistics. The categorical notions of linguistic stylistics also include: genres of language, predetermined by the communicative environment, the addresser (specificity of thinking), the recipient (linguistic-historical, linguistic and cultural experience), social, historical, cultural, and psychological context.
The dependence of style and genre varieties of language on the cultural and historical conditions of life of society, development of social forms of communication is explained. The connection between the linguistic stylistics of the text and the history of the literary language, and the hourly variations of literary norms is emphasized. The methods of linguistic and stylistic research, motivated by the theory of semasiology, cognitivism, pragmalinguistics and communicative linguistics are outlined.
The connotative semantics of the lingual structures of written and oral communication with the connection of these structures with psychology, collective consciousness, traditions of ethnoculture is determined.